Thalassaemia : a study on the perception of patients and family members - Jantan, Abdul Wahab; Muhammad, Siti Aeshah @ Naznin; Mat Zain, Nora; Abdul Rahman, Suzanah; Mohamed, Zulaiha; Abdul Rahim, Aidil Faszrul; Wan Su, Kamaruzaman (Malaysian Medical Association, 2011)
Marked improvement in the management of thalassaemia has not been matched by progress in psychosocial rehabilitation as thalassaemia continues to pose challenges to patients and their family members. Few studies have been carried out in Malaysia to look at such issues. This study is therefore to explore the concerns, beliefs and feelings about thalassaemia. It was conducted in the year 2009 over 7 months on “focus groups”, in patients aged 8-22 years and parents attending Paediatric Clinic of Tengku Ampuan Afzan Hospital, Kuantan, Pahang. Results showed that concerns and adverse impact were related to lower grades in education, poor self-image, less chance of employment, marriage, financial burden and social integration. Compliance to subcutaneous iron chelator was poor. There were various concerns related to blood transfusion therapy. It is evident that thalassaemia greatly affects the psychosocial dimensions and a more structured long term psychosocial support is needed to improve quality of life of patients.